A case series shows a relation between intracochlear electric field distribution and vestibular co-stimulation with cochlear implants - Luise Wagner; Torsten Rahne; Stefan K. Plontke; Laura Fröhlich (Scientific Reports)
Abstract The objective of this study was to investigate the relation between the electric field distribution within the cochlea during cochlear implant stimulation and the electrical vestibular co-stimulation measured by vestibular evoked myogenic potentials (e-VEMPs). Measurements were done in adult Nucleus cochlear implant (CI) users with perimodiolar electrode arrays. The electric field distribution within the cochlea was determined by Transimpedance Matrices recorded for all participants with a pulse width of 25 µs and a current level of 110 CL. Study measurements were conducted in 25 ears of 24 participants. In 10 participants, e-VEMPs could be elicited (40%). The occurrence of e-VEMPs stimulated by the cochlear implant was correlated with the magnitude of a corrected transimpedance at the most basal electrode. Since the results also suggest that there are patients with vestibular co-stimulation already present at their everyday CI stimulation level, this needs to be taken into account by audiologists creating programming maps for CIs, e.g. by deactivation of basal electrode contacts, if dizziness occurs during CI stimulation.